2021
DOI: 10.1590/0100-29452021710
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of fruits of varieties of mango (Mangifera indica) conserved in Peru

Abstract: The department of Piura is the main mango producer in Peru accounting for 66.7% of the national crop. The objective of the study was to characterize the fruits of forty varieties of mango preserved since 1969 in northwestern Peru. The fruits were harvested at the El Chira Agrarian Experimental Station, Department of Piura from December 2019 to January 2020. Thirteen quantitative fruit variables were evaluated: width, thickness, length, weight, seed width, seed thickness, seed length, percentage of seed, percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 4 publications
2
1
2
Order By: Relevance
“…However, these varieties from Mozambique had a stone thickness, 0.40 cm [36], significantly less. For the variety Kent cultivated in northwestern Peru, [37] reported stone length and thickness, respectively 8.05 cm and 2.05 cm, quite close to those obtained in this study; but these authors recorded a stone width, 3.65 cm, significantly less. According to [38], stone (endocarp) is generally flattened at the edges, more or less swollen in the middle, longer than wide.…”
Section: Morphological Characteristicssupporting
confidence: 88%
See 4 more Smart Citations
“…However, these varieties from Mozambique had a stone thickness, 0.40 cm [36], significantly less. For the variety Kent cultivated in northwestern Peru, [37] reported stone length and thickness, respectively 8.05 cm and 2.05 cm, quite close to those obtained in this study; but these authors recorded a stone width, 3.65 cm, significantly less. According to [38], stone (endocarp) is generally flattened at the edges, more or less swollen in the middle, longer than wide.…”
Section: Morphological Characteristicssupporting
confidence: 88%
“…In their study on varieties also cultivated in the north of Côte d'Ivoire, [23] reported higher fruit masses of Amelie and Kent, respectively 499.69 and 580.87 g, compared to our results; while fruit mass of Keitt was quite close to that recorded by these authors, which was 353.23 g. In previous work, several authors reported higher fruit masses compared to our results for Amelie, Kent and/or Keitt from Burkina Faso [41], Nigeria [42], Cameroon [34], Mozambique [36], Egypt [43] and Peru [37]. Nevertheless, the three varieties studied can all be exported to the European market because their fruit masses correspond to the caliber group B established by the mango standard [44].…”
Section: Physical Characteristicssupporting
confidence: 86%
See 3 more Smart Citations